International Journal of Chemotherapy and Practice; A Novel Journal for Therapeutic Researches - Cagri Oner (International Journal of Chemotherapy Research and Practice, 2018)
An inaugural editorial presents the journal's scope spanning chemotherapy research and clinical practice. It invites translational work linking mechanisms, regimens, and real‑world outcomes with an emphasis on safety and effectiveness.